ESSAYISTIC SELECTIONS OF DANILO KIŠ (Heritage, 2020)
Evaluation of the essayistic opus of Danilo Kiš and his authorial choices, if we exclude one scientific paper by R. Ivanović, dedicated to the book Po-ethics, has not been the subject of a serious discussion so far, although the critics mostly agreed that he is a world writer. The subject of interest of this paper are the selections of essay texts that Kiš published during his lifetime in the books Po-ethics (1972), Po-ethics, book two (1974) and Homo poeticus (1983). The research focus is on the composition and structure of books – criteria for the selection and arrangement of texts, the logic of their content, the level of authorial self-criticism and representativeness. When making a judgment about the objectivity of Kiš as the compiler of these selections, essays that for various reasons remained outside the covers of the mentioned books are also taken into consideration – their literary-aesthetic, cognitive, cultural and autopoetic value. The composition of the book Anatomy Lesson, although in the genealogical sense it is a book-essay, deserves a special study, and therefore is not the subject of analysis of this paper. Key words: essay writing, selection, criterion, self-criticism, representativeness, evaluation, Po-ethics (1972), Po-ethics, book two (1974), Homo poeticus (1983)
Keywords: Key words: essay writing, selection, criterion, self-criticism, representativeness, evaluation, Po-ethics (1972), Po-ethics, book two (1974), Homo poeticus (1983)